PENINGKATAN PROFESIONALISME GURU KELOMPOK BERMAIN SRIKANDI ROWODADI - Retno Wulandari; Mayang Belia Sameto; Sumantri (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2023)
Professional teachers can produce students who are competent and compete in this era of globalization. In line with the motto of KB Sebiduk Sehaluan Srikandi, "Smart Generation, Love Al-Qur'an", teachers must be professional and competent in carrying out their duties. Efforts to improve teacher professionalism made by principals are to include teachers in various activities such as; educational seminars, tiered training, and interactive talks are one of the activities routinely carried out by principals and teachers. The result is that through interactive talks, teachers can more freely express the obstacles that hinder teachers' professionalism in teaching, as principals are also easier to identify problems, find solutions to problems.